Perceptions of MSC. learning sciences graduates on the program - Sim, Philip Zhi Liang (Universiti Malaysia Sarawak (UNIMAS), 2015)
The study traced UNIMAS MSc. Learning Sciences graduates to find out their perceptions on the program, specifically on the individual courses offered, how the program has impacted on their works, careers and lives; and also to capture comments on how the program could be further improved. Open-ended questionnaires were emailed to 9 respondents who were selected through the Snowballing method. and the data were coded to highlight potential areas of improyement. The fmdings showed that on overall, graduates are satisfied with the courses offered, and they have experienced positive changes in their works, careers and lives. Nevertheless, a few issues were discovered, and suggestions were made in order to rectify or improve the program. Future researches could focus on addressing the gap of increasing the value of the program to non-teaching professions.